2003
DOI: 10.1637/5917
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Turkey Coronavirus in Turkeys and Chickens

Abstract: We designed this study to compare the replication potential of turkey coronavirus (TCV) and its effect in chickens and turkeys and to study the effect of singleand combined infection of turkey poults with TCV and astrovirus. We studied the pathogenicity of TCV in experimentally inoculated turkey poults and chickens by observing the dinical signs and gross lesions. Two trials were conducted with 1-day-old and 4-wk-old specific-pathogen-free turkey poults and chickens. One-day-old turkey poults developed diarrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
69
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 20 publications
(9 reference statements)
11
69
1
1
Order By: Relevance
“…Thus, avian coronavirus from one species has been shown to replicate in other avian species without observation of clinical signs in most instances [13,15]. Chickens are the main natural hosts of IBV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, avian coronavirus from one species has been shown to replicate in other avian species without observation of clinical signs in most instances [13,15]. Chickens are the main natural hosts of IBV [5].…”
Section: Introductionmentioning
confidence: 99%
“…From both practical and academic viewpoints, it is important to understand the extent to which an avian coronavirus from one species can replicate in another. Although it has been shown that an avian coronavirus from one species can replicate in other avian species, no clinical signs are observed in most instances (Lister et al, 1985;Guy, 2000;Ismail et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…From both practical and academic viewpoints, it is important to understand the extent to which an avian coronavirus from one species can replicate in another. Although it has been shown that an avian coronavirus from one species can replicate in other avian species, no clinical signs are observed in most instances (Lister et al, 1985;Guy, 2000;Ismail et al, 2003).In order to investigate the extent to which coronaviruses can replicate in bird species beside chickens, turkeys, pheasants, pigeons and guineafowl, 55 specimens from four avian species were collected from apparently healthy domestic bird flocks in Guangdong province, China, in 2003. These specimens were tested for the presence of coronaviruses by using RT-PCR (Stephensen et al, 1999) and virus isolation in 9-to 11-day-old specific-pathogenfree (SPF) chicken embryos.…”
mentioning
confidence: 99%
“…It has been shown previously that birds infected with TCoV usually demonstrate poor growth rate compared with uninfected poults of the same age (Brown et al, 1997;Breslin et al, 2000;Guy et al, 2000;Ismail et al, 2003). Turkeys infected with TCoV can demonstrate depression, anorexia and decreased water consumption associated with dehydration, watery diarrhoea and poor growth performance (Guy, 2003;Cavanagh, 2005;Teixeira et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…TCoV can spread rapidly via the faecalÁoral route (Naqi et al, 1972) and can infect turkey at different ages, resulting in high morbidity and varying mortality. Affected birds usually have diarrhoea, ruffled feathers, decreased feed and water consumption in addition to poor growth rate (Barnes et al, 1997;Yu et al, 2000;Ismail et al, 2003). Even after the disappearance of the clinical signs, infected birds can still shed TCoV particles in their droppings up to 7 weeks post infection (Larsen, 1979;Breslin et al, 2000, Gomaa et al, 2009.…”
Section: Introductionmentioning
confidence: 99%